EFEKTIVITAS REZIM COMFORT WOMEN AGREEMENT ANTARA JEPANG DAN REPUBLIC OF KOREA (ROK) DALAM PENYELESAIAN MASALAH JUGUN IANFU DI REPUBLIC OF KOREA (ROK) - Firda Ainun Ula; Yeyen Subandi; Diansari Solihah Amini; Tanti Nurgiyanti; Bagus Subekti Nuswantoro; Harits Dwi Wiratma (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2023)
The Comfort Women incident that occurred during World War II is a historical issue that continues to overshadow the relationship between the two countries between the Republic of Korea (RoK) and Japan. On December 28, 2015 RoK and Japan carried out reconciliation which officially agreed on the Comfort Women Agreement as a resolution that was 'Finaland Irreversible'. However, disappointment arose after the Comfort Women Agreement was agreed upon by the Jugun Ianfu, even though the Japanese side greatly appreciated and supported the reconciliation efforts. This study aims to analyze how the effectiveness of the regime after the Comfort Women Agreement was officially agreed upon in resolving the problems of comfort women by using the analytical framework of Arild Underdal's theory about regime effectiveness. The research was conducted using qualitative methods and analyzed the responses from the RoK countries and Japan after the Comfort Women Agreement was agreed in an effort to resolve the problems of comfort women through Output, Outcome, and Impact. This study found that there were differences in response in efforts to resolve the comfort women's problem between RoK and Japan after the Comfort Women Agreement was agreed. The survivors of Jugun Ianfu with an alliance of civil society rejected the outcome of the Comfort Women Agreement.